Vaginal surgery - Cosson, Michel; Querleu, Denis; Dargent, Daniel; Blanchet, Guillaume (Taylor & Francis, 2005)
Surgical techniques that take advantage of the vaginal route are now used quite widely. The advantages of this approach are numerous: patient comfort, aesthetic results and, above all, reduced post-operative morbidity. In addition, the time necessary for hospitalization and convalescence are reduced, and that using instruments less onerous than those required for laparoscopy. Nevertheless, the application of this technique requires expertise, training, and experience. This is why this reference, resolutely didactic and practical, was written with the ambition to become a handbook of reference for the proven techniques of vaginal surgery.
Keywords: Vaginal Diseases; inkontinence moči; nádory vaginy; vaginální onemocnění; Vagina; vagina; Urinary Incontinence; chirurgie; gynekologie a porodnictví; Vaginal Neoplasms